Penerapan Model Pembelajaran Snowball Throwing terhadap Hasil Belajar PKN Siswa Kelas V - Aulia, Novera Putri; Prananosa, Ahmad Gawdy; Frima, Aren (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine whether applying the snowball-throwing learning model can complete the learning outcomes of students in grade V of SD Negeri 23 Lubuklinggau. This type of research is quantitative with a quasi-experimental method. Based on the results of the study showed that the average pre-test score was 44.00. After the Snowball Throwing learning model was applied to the material of community harmony and the benefits of unity and oneness in PKN lessons, the post-test results showed an average score of 85.35 and the number of completions reached 85%. If the hypothesis Zcount> Ztable (5.97> 1.64) with a confidence level of α = 0.05 which means Ho is rejected and Ha is accepted, then the average value of the learning outcomes of students in grade V of SD Negeri 23 Lubuklinggau after the Snowball Throwing learning model was applied significantly completed. Keywords: Learning Outcomes, Elementary School, Snowball Throwing